Connecting networks course booklet - Cisco Networking Academy (Indianapolis : Cisco Press, 2013)
Connecting Networks is the first course of the updated CCNA v5 curriculum offered by the Cisco Networking Academy. This course is intended for students who are beginners in networking and pursuing a less technical career. The Connecting Networks Course Booklet offers a new way for students enrolled in a Cisco Networking Academy introduction to Networking course to easily read, highlight, and review on the go, wherever the Internet is not available. The text is extracted directly from the online course, with headings that have exact page correlations to the online course. An icon system directs the reader to the online course to take full advantage of the images, labs, Packet Tracer activities, and dynamic Flash-based activities. The books are intended to be used with the course.